Impacts of road pricing upon travel demand in an integral city region: A case study of London and its surrounding regions - Ying Jin (European Regional Science Association (ERSA), 2010)
This paper aims to study ways in which the impacts of road pricing upon travel demand can be examined in the wider city region, with a view to inform the design and possible future adaptations of road charges. Its theoretical framework incorporates the medium to long term impact of transport costs (including road charging) upon business location and commuting patterns. A case study is carried out on London and its surrounding regions, through a review of existing evidence and a set of simulation tests using a land use/transport model that has been calibrated to represent realistic travel demand elasticities. The new feature of these simulation tests is that they account for business productivity effects as well as land use/transport interaction. A generic, city-region wide marginal social cost pricing scheme is estimated together with different land use development scenarios to identify directions and range of the effects. The model results show that the social marginal cost based road pricing scheme can have significant long term impacts upon travel demand if they trigger land use changes, which could either enhance or negate the initial travel time savings and reliability benefits. Note: an extended abstract has been previously submitted via email to convenor.
Keywords: 330